Interplay Between Cytokine-Induced and Cyclic Equibiaxial Deformation-Induced Nitric Oxide Production and Metalloproteases Expression in Human Alveolar Epithelial Cells - Patel, Hemang (2009)
Ventilator-induced lung overdistension has been a growing concern in the management of mechanically ventilated patients. Mechanical ventilation triggers or enhances the net inflammatory and tissue remodeling activities. Although it has been shown that proinflammatory and tissue remodeling factors play important roles during airway remodeling, the interplay between them is not well understood. Thus, our objective was to study and characterize the molecular mechanism of cyclic equibiaxial deformation-induced airway inflammation and remodeling either in the presence or absence of a pre-existing inflammatory condition. This study was done using an in vitro dynamic model, which can simulate different mechanical ventilative conditions. Type II alveolar epithelial cell (A549) monolayers were exposed to the different levels of mechanical ventilative conditions using the Flexcell(®) Tension Plus(™) 4000T system, which generated the different levels of cyclic equibiaxial deformation (5, 10, 15, and 20%) at 0.2 Hz deformation frequency. The production of nitric oxide (NO), the expression of metalloprotease-2 (MMP-2)/tissue inhibitor metalloprotease-2 (TIMP-2), and the activation of MMP-2 were measured under the different levels of cyclic equibiaxial deformation either in the presence or absence of TNF-α. Our study indicated that cyclic equibiaxial deformation-induced production of NO and MMP-2/TIMP-2. Higher levels of cyclic equibiaxial deformation increased the expression of the active form of MMP-2. In particular, in the presence of TNF-α, the more active form of MMP-2 was detected during both cyclic equibiaxial deformation and remodeling periods.